The CCR2/MCP-1 Chemokine Pathway and Lung Adenocarcinoma - Mittal, Payal (Cancers (Basel), 2020)
SIMPLE SUMMARY: Myeloid-derived suppressor cells (MDSCs) are present at the sites of many solid tumors and dampen host immune responses. We studied how these MDSCs accumulate and how this process might be interrupted using lung cancer cell lines growing in immunocompetent mice. We found that tumor cells release a chemokine, MCP-1, that attracts MDSCs as a result of their expression of the MCP-1 receptor, CCR2. We showed that mice lacking CCR2, or the use of a small-molecule inhibitor of CCR2, prevented MDSC recruitment to the tumors and derepressed host T cell responses, allowing immune activation and inhibition of tumor growth. These data suggest that CCR2 inhibitors may be a new tool for cancer immunotherapy. ABSTRACT: Host anti-tumor immunity can be hindered by various mechanisms present within the tumor microenvironment, including the actions of myeloid-derived suppressor cells (MDSCs). We investigated the role of the CCR2/MCP-1 pathway in MDSC-associated tumor progression in murine lung cancer models. Phenotypic profiling revealed maximal expression of CCR2 by tumor-resident MDSCs, and MCP-1 by transplanted TC1 tumor cells, respectively. Use of CCR2-knockout (CCR2-KO) mice showed dependence of tumor growth on CCR2 signaling. Tumors in CCR2-KO mice had fewer CCR2(low) MDSCs, CD4 T cells and Tregs than WT mice, and increased infiltration by CD8 T cells producing IFN-γ and granzyme-B. Effects were MDSC specific, since WT and CCR2-KO conventional T (Tcon) cells had comparable proliferation and production of inflammatory cytokines, and suppressive functions of WT and CCR2-KO Foxp3+ Treg cells were also similar. We used a thioglycolate-induced peritonitis model to demonstrate a role for CCR2/MCP-1 in trafficking of CCR2+ cells to an inflammatory site, and showed the ability of a CCR2 antagonist to inhibit such trafficking. Use of this CCR2 antagonist promoted anti-tumor immunity and limited tumor growth. In summary, tumor cells are the prime source of MCP-1 that promotes MDSC recruitment, and our genetic and pharmacologic data demonstrate that CCR2 targeting may be an important component of cancer immunotherapy.